Blue's clues. Blue talks - Patton, Donovan; Johnson, Traci Paige (Hollywood, Calif. : Paramount, 2004)
A collection of episodes in which Blue, the puppy, begins to speak.
The legend of the blue puppy -- Love day -- Bonus episodes: Blue's big mystery ; Periwinkle misses his friend.
Features: welcome to B-B-B-Blue's room game, sneak peeks, Blue's room shorts "Friends songs," and "Roaring lessons."
Donovan Patton ; Voice: Traci Paige Johnson.
Ages 3-7.
DVD, Dolby digital 2.0 stereo.
Closed-captioned.
Keywords: Dogs -- Juvenile drama; Play -- Juvenile drama; Video recordings for hard of hearing people; Television programs; Dogs -- Drama; Play -- Drama; Children's television programs